Multimodal management and complete resection of invasive Type B3 thymoma with vascular reconstruction: a case report - Puiyee Sophia Chan; Akshay J. Patel; Gianluca Lucchese; Andrea Bille (Journal of Cardiothoracic Surgery)
Abstract Introduction Thymomas and thymic carcinomas are rare anterior mediastinal tumours, accounting for 0.2–1.5% of all cancers. Surgical resection is key to treatment, though invasion of surrounding structures like great vessels can complicate this. This case report details the management of a type B3 thymoma (T4 N0 M0) in a 41-year-old male. Case report A 41-year-old male presented with myasthenic symptoms and was diagnosed with a large thymic mass involving the brachiocephalic vein and superior vena cava. After 4 cycles of neoadjuvant chemotherapy, partial resection was performed, followed by radiotherapy. Residual disease led to a second surgery, during which tumour resection and vascular reconstruction using cardiopulmonary bypass were successfully completed. Postoperative recovery was uneventful. Discussion Complete resection, including re-resection, when necessary, is crucial for improved outcomes in thymoma patients. Even with great vessel invasion, aggressive surgery, coupled with chemotherapy and vascular reconstruction, can achieve good survival outcomes. Conclusion Multimodal management, including chemotherapy, complete resection, and vascular reconstruction, offers the best prognosis for invasive thymomas, even with great vessel involvement.